Internet technologies and information services - Miller, Joseph B. (Westport, Conn. : Libraries Unlimited, 2009)
This book is organised around three main areas. Part 1 is on network and internet technologies, part 2 considers web design and technologies and part 3, is on internet content, information retrieval, and search engines covering the the documentary formats for internet content.
Includes bibliographical references (p. 363-375) and index.
osc03/05/13
Loans
Keywords: Libraries and the Internet; Internet technologies; Information services; Libraries